The Interplay Between Epigenetic Regulation and CD8+ T Cell Differentiation/Exhaustion for T Cell Immunotherapy - Wong, Wai Ki; Yin, Bohan; Lam, Ching Ying Katherine; Huang, Yingying; Yan, Jiaxiang; Tan, Zhiwu; Wong, Siu Hong Dexter (Frontiers in Cell and Developmental Biology, 2022)
Effective immunotherapy treats cancers by eradicating tumourigenic cells by activated tumour antigen-specific and bystander CD8+ T-cells. However, T-cells can gradually lose cytotoxicity in the tumour microenvironment, known as exhaustion, which acquires effector function and restricts differentiation potential. Recently, DNA methylation, histone modification, and chromatin architecture have provided novel insights into epigenetic regulations of T-cell differentiation/exhaustion, thereby controlling the translational potential of the T-cells. Thus, developing strategies to govern epigenetic switches of T-cells dynamically is critical to maintaining the effector function of antigen-specific T-cells. In this mini-review, we (1) describe the correlation between epigenetic states and T cell phenotypes; (2) discuss the enzymatic factors and intracellular/extracellular microRNA imprinting T-cell epigenomes that drive T-cell exhaustion; (3) highlight recent advances in epigenetic interventions to rescue CD8+ T-cell functions from exhaustion. Finally, we express our perspective that regulating the interplay between epigenetic changes and transcriptional programs provides translational implications of current immunotherapy for cancer treatments.